Short Communication: Weak delineation of Styrax species growing in North Sumatra, Indonesia by matK + rbcL gene - ARIDA SUSILOWATI; HENTI HENDALASTUTI; CUT RIZLANI KHOLIBRINA; RINI RAMADHANI (Society for Indonesian Biodiversity, 2017)
Susilowati A, Hendalastuti H, Kholibrina CR, Ramadhani R. 2017. Weak delineation of Styrax species growing in North Sumatra, Indonesia by matK + rbcL gene. Biodiversitas 18: 1270-1274. The aim of DNA barcoding is to enable precise identification of species from analysis of a unique DNA sequence of a target gene. The present study was undertaken to develop barcodes for different species of Styrax L. growing in North Sumatra, Indonesia. Four putative species of Styrax (each represented by specimens collected from two districts in North Sumatra) were evaluated using two regions in the plastid genome (matK and rbcL) in order to discriminate them at species level. Results showed that matK yielded 891 bp after alignment, however there was no precise identification to species level. The matK gene only differentiated the four recognized species into two groups, each group consisted of two of the species. The rbcL gene yielded 588 bp and showed no variation between species: that is,it determined all the currently recognized species to be of one and the same haplotype. Furthermore, combined matK + rbcL gave a similar grouping result to that for the matK gene considered alone. Considering the overall performance of these loci, we suggest matK + rbcL is not strong enough to determine Styrax growing in North Sumatra to the species level as distinguished on morphological grounds. These findings show the necessity of finding other candidate genes or markers that can potentially be helpful in delineating the various species of Styrax growing in North Sumatra, as well as other related Styrax genera.